$\displaystyle \mathbf {(AB)}_{ik} = \sum_{1 \le j \le n}a_{ij}b_{jk}$, call this $(1)$. Let $\mathbf{A} \mapsto \mathbf{AB}$ and $\mathbf{B} \mapsto \mathbf{C}$ and reindexing we've $\displaystyle (\mathbf{(AB)C})_{i\ell} = \sum_{1 \le k \le n}(\mathbf{AB})_{ik}c_{k \ell} = \sum_{1 \le k \le n}\bigg(\sum_{1 \le j \le n}a_{ij}{b_{j k}}\bigg) c_{k \ell} =\sum_{1 \le k \le n}\sum_{1 \le j \le n}a_{ij}{b_{j k}} c_{k \ell}$.
Now, this time letting $\mathbf{B} \mapsto \mathbf{BC}$ in $(1)$ reindexing again similarly we end up with